2021
DOI: 10.1002/ijfe.2520
|View full text |Cite
|
Sign up to set email alerts
|

Controlling shareholders' influence on acquisition decisions and value creation: An empirical study from China

Abstract: Controlling shareholders are capable of influencing major decisions in firms, and their existence may give rise to principal‐to‐principal conflict as minority shareholders may feel sidelined during decision‐making. This study employs a proxy (the highest control right), which takes into consideration both direct and indirect controls to investigate the excess cash usage preference of controlling shareholders. Again, the study investigates how the background characteristics of different controlling shareholders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…First, we perform a multivariate probit regression to analyse the event in which corporate investors fund companies. Having a dichotomous dependent variable, we follow Opoku‐Mensah and Yin (2021) in using a multivariate probit model. Khan et al (2021) recommend this as an appropriate approach due to the correlation between independent variables, indicating the nature of the normal distribution of the data.…”
Section: Methodology and Data Descriptionmentioning
confidence: 99%
“…First, we perform a multivariate probit regression to analyse the event in which corporate investors fund companies. Having a dichotomous dependent variable, we follow Opoku‐Mensah and Yin (2021) in using a multivariate probit model. Khan et al (2021) recommend this as an appropriate approach due to the correlation between independent variables, indicating the nature of the normal distribution of the data.…”
Section: Methodology and Data Descriptionmentioning
confidence: 99%
“…PP conflicts may arise when controlling shareholders maximize their private benefits by exploiting the wealth of minority shareholders. Scholars have suggested that controlling shareholders maximize private benefits through dividend cuts, excessive cash holdings, tax avoidance, inefficient investments, and related-party transactions (Bauer et al, 2020;Faccio et al, 2001;Huyghebaert & Wang, 2012;Jebran et al, 2019;Jiang et al, 2015Jiang et al, , 2018Opoku-Mensah & Yin, 2021). Additionally, PP conflicts may result in additional agency costs, which may reduce the performance and value of the company (Cronqvist & Nilsson, 2003;Ferris et al, 2003;Morck et al, 2005;Sauerwald et al, 2019).…”
Section: Pp Conflicts and Stakeholder-oriented Corporate Governancementioning
confidence: 99%
“…Hence, our incentive is characterized as a typically used progressive incentive, which is more applicable in the Chinese labour market than a regressive one. Opoku‐Mensah and Yin (2021) find that controlling shareholders in the Chinese listed firms are more likely to influence the use of excess cash into acquisition activities other than to retain such cash in the firm possibly for the payment of a dividend. Because of the under‐developed financial market, the controlling shareholders can apply progressive incentive.…”
Section: The Modelmentioning
confidence: 99%